Chronic Physical and Mental Health Conditions Associated With Employment Status in Veterans - Kavita Mosalpuria, PhD; Elise V. Bailey, BS; Hyunkyu Ko, PhD; Eric J. Hansen, BS; Fernando A. Wilson, PhD (Elsevier, 2024)
Introduction: Veterans commonly experience both poor health and employment difficulty. However, the research examining potential relationships between chronic physical and mental health conditions and employment in veterans has important limitations. This study examines those potential relationships using large-scale, nationally representative data. The authors' hypothesis was that veterans experiencing these conditions would be less likely to be employed than veterans without the conditions and, further, that there may be differences in these relationships when comparing male veterans with female veterans. Methods: The study team conducted a pooled cross-sectional analysis of nationally representative data from the 2004-2019 administrations of the Medical Expenditures Panel Survey, which had items addressing health conditions, employment, and military experience. The authors assessed the relationship between health conditions and employment using multivariate logistic regression. Control variables included demographics, SES, family size, and survey year. Results: Veterans experiencing diabetes, high blood pressure, stroke, emphysema, arthritis, serious hearing loss, poor self-reported mental health, poor self-reported health, depression, or psychological distress were less likely to be employed than veterans without those conditions, even after adjusting for potential confounding factors. Veterans with diabetes had 25% lesser odds of being employed than veterans without the condition (95% CI=0.65, 0.85). Veterans with increased likelihood of depression had 35% lesser odds of being employed than veterans without depression (95% CI=0.52, 0.81). Conclusions: This study adds evidence to the understanding of the role of chronic health conditions in employment status of veterans. The results support arguments for programs that aid veterans with both their health and their employment.